Uderground Mine DOZ "Deep Ore Zone" PT Freeport Indonesia: Improvisasi Pencampuran Dan Penarikan Material Basah dan Kering Pada Level Ekstraksi & Haulage Tambang Bawah Tanah DOZ PT. Freeport Indonesia - Wabes, Albert; WIJAYA, ANDY ERWIN (ReTII, 2022)
Indication of changes in daily target gains decreased in February - May 2019, causing personal interest in dissecting the anomaly further. This anomaly greatly affects the annual achievement of DOZ tonnage production per day, so this has a very significant impact because the range of tons loss in the period from February to May 2019 is very varied which is around 10.000 tpd from the daily production plan of 37.000tpd. This is considered important and needs a more detailed study by paying attention to the DOZ production chart per day and trying to look deeper into the contributors to the achievement. There are 10 indicators as a source of down time (delay) that causes economic achievement by Ore Slide activity and Down Stream. As a result of the delay the impact is the lose of the opportunity to get (lose opportunity) the metal price that has been forecast. This opportunity long range for Aurum (Au) Rp.30.105.600.000,- per day and cuprum (Cu) around 3.857.000.000 per day. The loss of this opportunity against the previous 3 months (November 2018, December 2018 & January 2019) was around Rp.6.758.557.400.000 billion),- In order no to lose in the future with the exiting forecast reference of 37,000 tpd, the strategy applied is the Blending Method (a method of mixing dry muck with wet muck) considered quite applicable by not affecting the current Sources. Key Word: lose opportunity , ore slide, blending method